World Statistics Pocketbook 2015 - United Nations (United Nations, 2015)
This edition of the World Statistics Pocketbook is the thirty-third in a series of annual compilations of key statistical indicators prepared by the United Nations Statistics Division of the Department of Economic and Social Affairs. Over 50 indicators have been collected from more than 20 international statistical sources, and are presented in one-page profiles for over 200 countries or areas of the world. This issue covers various years from 2005 to 2015. For the economic indicators, in general, three years – 2005, 2010 and 2013 – are shown; for the indicators in the social and environmental categories, data for one year are presented. The topics covered include: agriculture, balance of payments, education, energy, environment, food, gender, health, industrial production, information and communication, international finance, international tourism, international trade, labour, migration, national accounts, population and prices.